A Assistance for micro businesses in processing rice bran as alternative nutrition to prevent stunting - Awatiful Azza; Nikmatur Rohmah; Ara Nugrahayu Nalawati (UNUSA Press, 2023)
Stunting is a condition that can interfere with the growth and development of children. There are several causes of stunting, including the lack of high nutritional intake by pregnant women. Rice bran is one of the processed rice wastes which has nutritional content and is very good for health, which can be used as an alternative nutritional basis for pregnant women. Until now, the use of rice bran as an alternative nutrient has not been optimally utilized by the people in Silo village. The purpose of this activity is to assist micro businesses in processing rice bran as an alternative nutrition to prevent stunting. This activity was carried out in the home industry group